Beginning Google SketchUp for 3D printing - Singh, Sandeep (Expert's voice in 3D printing., 2010)
"Beginning Google SketchUp for 3D Printing starts by explaining how to use SketchUp and itsplug-ins to make your design products. You will learn how to present and animate 3D models, and how to use Google Earth and 3D Warehouse to sell and market your 3D models. You'll also get a vision of the future of 3D printing so you can plan your future projects while mastering today's tools"--Page 4 of cover